Targeting a cancer-specific LYPD3 glycoform for tumor therapy - Neumann, Theresa; Hartung, Evelyn; Gellert, Johanna; Weiß, Lisa; Weiske, Manon; Kast, Naomi; Gurka, Stephanie; Marinoff, Sophie; Jäkel, Anika; Danielczyk, Antje; Kehler, Patrik (Frontiers in Drug Discovery, 2023)
One of the most drastic changes in cancer is the altered glycosylation of proteins and lipids, giving rise to truncated O-glycans like the Thomsen Friedenreich (TF) or Thomsen nouvelle (Tn) antigen, which are almost absent on normal cells. Combined protein-carbohydrate epitopes comprising these specific glycans are ideal candidates for potent targeted therapies given their excellent tumor specificity and broad cancer expression. We have generated GT-002, a monoclonal antibody specifically targeting the epithelial glycoprotein LYPD3 only in the presence of a TF glycosylation. It does not cross-react with non-glycosylated LYPD3 or TF on other glycoproteins in ELISA and flow cytometry. GT-002 binds to various tumor cell lines and stains tumor tissues of different cancer indications including squamous cell carcinoma of the head and neck. The remarkable tumor specificity was confirmed in an immunohistochemistry study on a normal human tissue panel including several LYPD3-positive organs, where GT-002 elicited almost completely abolished normal tissue binding. Consequently, we observed markedly reduced binding of GT-002 to normal human tissues compared to Lupartumab, a conventional anti-LYPD3 antibody previously in clinical development as antibody-drug conjugate (BAY1129980). Neuraminidase treatment of healthy tissues, resulting in cleavage of sialic acid residues, re-established binding of GT-002 comparable to Lupartumab, showing that the GT-002 epitope is masked by sialic acid in normal cells.We believe that GT-002 is a promising candidate for development of antibody-drug-and radioconjugates as well as bispecific molecules and chimeric antigen receptor therapeutics and highlights the powerful potential of antibodies against combined protein-carbohydrate epitopes to reduce ontarget/off-tumor cytotoxicity.